Morbidity of total pancreatectomy with islet cell auto‐transplantation compared to total pancreatectomy alone. Issue 6 (29th August 2013) - Bhayani, Neil H.; Enomoto, Laura M.; Miller, Jennifer L.; Ortenzi, Gail; Kaifi, Jussuf T.; Kimchi, Eric T.; Staveley‐O'Carroll, Kevin F.; Gusani, Niraj J.
Abstract Background In pancreatitis, total pancreatectomy (TP) is an effective treatment for refractory pain. Islet cell auto‐transplantation (IAT) may mitigate resulting endocrinopathy. Short‐term morbidity data for TP + IAT and comparisons with TP are limited. Methods This study, using 2005–2011 National Surgical Quality Improvement Program data, examined patients with pancreatitis or benign neoplasms. Morbidity after TP alone was compared with that after TP + IAT. Results In 126 patients (40%) undergoing TP and 191 (60%) patients undergoing TP + IAT, the most common diagnosis was chronic pancreatitis. Benign neoplasms were present in 46 (14%) patients, six of whom underwent TP + IAT. Patients in the TP + IAT group were younger and had fewer comorbidities than those in the TP group. Despite this, major morbidity was more frequent after TP + IAT than after TP [n = 79 (41%) versus n = 36 (29%); P = 0.020]. Transfusions were more common after TP + IAT [n = 39 (20%) versus n = 9 (7%); P = 0.001], as was longer hospitalization (13 days versus 9 days; P < 0.0001). There was no difference in mortality. Conclusions This study is the only comparative, multicentre study of TP and TP + IAT. The TP + IAT group experienced higher rates of major morbidity and transfusion, and longer hospitalizations. Better data on the longterm benefits of TP + IAT are needed. In the interim, this study should inform physicians and patients regarding the perioperative risks of TP + IAT.